2015
DOI: 10.1073/pnas.1512092112
|View full text |Cite
|
Sign up to set email alerts
|

Structure and control of charge density waves in two-dimensional 1T-TaS 2

Abstract: The layered transition metal dichalcogenides host a rich collection of charge density wave phases in which both the conduction electrons and the atomic structure display translational symmetry breaking. Manipulating these complex states by purely electronic methods has been a long-sought scientific and technological goal. Here, we show how this can be achieved in 1T-TaS 2 in the 2D limit. We first demonstrate that the intrinsic properties of atomically thin flakes are preserved by encapsulation with hexagonal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
259
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(292 citation statements)
references
References 26 publications
24
259
4
Order By: Relevance
“…The off-diagonal hopping matrix elements between the same type of atoms (M-M and X-X) can be classified into two categories depending on the symmetry of the i and j orbitals under M 2 : for (i,j )=(3,5), (6,8), (9,11), the symmetry is (+), giving (5) while for (i,j )=(1,2), (3,4), (4,5), (6,7), (7,8), (9,10), (10,11), the symmetry is (−), giving…”
Section: Index Basis Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The off-diagonal hopping matrix elements between the same type of atoms (M-M and X-X) can be classified into two categories depending on the symmetry of the i and j orbitals under M 2 : for (i,j )=(3,5), (6,8), (9,11), the symmetry is (+), giving (5) while for (i,j )=(1,2), (3,4), (4,5), (6,7), (7,8), (9,10), (10,11), the symmetry is (−), giving…”
Section: Index Basis Functionmentioning
confidence: 99%
“…while for the pairs (i,j )=(4,1), (3,2), (5,2), (9,6), (11,6), (10,7), (9,8), (11,8), the symmetry is (−), giving…”
Section: Index Basis Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al reported a gate-controlled Li ion intercalation can suppress CCDW and introduce superconducivity [21]. Tsen et al [22], Hollander et al [23], Yoshida et al [24], and Mihailovic et al [25,26] reported the in-plane electric field induced transition from CCDW state to NCCDW or some metastable hidden state. Cho et al applied perpendicular electric pulse on 1T -TaS 2 and found positive electric pulse can introduce IC network to suppress Mott state at low temperature [27].…”
Section: Introductionmentioning
confidence: 99%
“…1(b) shows an optical image of a representative device with the MoTe2 flake outlined by a dashed line. In order to avoid the effects of surface oxidation [26][27][28], MoTe2 was exfoliated onto a polymer stamp within a nitrogen-filled glovebox, transferred onto gold electrodes, and covered with hexagonal boron nitride (hBN) before being moved out to the ambient environment. Since hBN conforms to the features of the underlying surface, an atomic force microscope was used to determine the thickness of the buried MoTe2.…”
mentioning
confidence: 99%